Quantification in than-clauses - Krasikova, Sveta (Proceedings of the Amsterdam Colloquium, 2007)
This study proposes a solution to the problem of the non-homogeneous behaviour of quantifiers in comparative clauses. An interval-based approach is used for the implementation of the analysis. It is argued that the so-called scope splitting modals, exemplified by have to, trigger the insertion of a covert exhaustivity operator of the kind proposed in Fox 2006 that is restricted by a set of alternatives ranked on a likelihood/effort scale. This explains the availability of more-than-min and more-than-max readings with have to. The present analysis also accounts for the fact that existential quantifiers, except for the polarity-sensitive indefinites and possibility modals, are not interpreted under the comparative.